Trait hierarchies and intraspecific variability drive competitive interactions in Mediterranean annual plants. (19th August 2019) - Carmona, Carlos P.; de Bello, Francesco; Azcárate, Francisco M.; Mason, Norman W. H.; Peco, Begoña
Abstract: Both intra‐ and interspecific differences in traits may modulate interactions between plants. Two mechanisms are hypothesized to regulate these effects: competitive hierarchies and trait dissimilarities, but it is unclear how the prevalence of each might depend on environmental conditions and on intra and interspecific differences. We sowed six replicates of all possible pairwise combinations across eight annual species (including conspecific competition and individuals without competitors), in pots under two levels of fertilization. We measured above‐ and below‐ground traits and total biomass of the focal individuals. We expressed competition as the decrease in biomass of focal individuals relative to biomass without competition, and modelled competition using directional (hierarchy) or non‐directional (dissimilarity) trait differences, with or without intraspecific variability (ITV). We found evidence of different trait hierarchies operating under different fertilization conditions but little support for trait dissimilarities. The negative effect of competition on focal plants increased with the height of the competitors in both of fertilization levels. Further, in unfertilized conditions, plants with lower specific leaf area (SLA) and larger root systems experienced less competition. Including ITV in trait hierarchies substantially improved our ability to predict the intensity of competition. This was partly due to ITV reducing competitive hierarchies. Synthesis . Our results underscore the importance of traits in driving interactions among plants. Competitive relationships between species depend on complex interactions between trait intra and interspecific differences and resource availability. ITV appears to be a mechanism capable of reducing trait hierarchies, and hence the intensity of competition between coexisting plants. Abstract : Our results underscore the importance of traits in driving interactions among plants. Competitive relationships between species depend on complex interactions between trait intra and interspecific differences and resource availability. ITV appears to be a mechanism capable of reducing trait hierarchies, and hence the intensity of competition between coexisting plants. Abstract in Spanish: Las diferencias intra‐ e interespecíficas en atributos funcionales pueden afectar a las interacciones entre plantas. En teoría, dos mecanismos pueden regular estos efectos: las jerarquías competitivas y la disimilitud en atributos, pero no esta claro como la prevalencia de cada uno de estos mecanismos depende tanto de las condiciones ambientales como de las diferencias intra e interespecíficas. Seis réplicas de todas las posibles combinaciones de parejas de ocho especies anuales típicas de pastizales mediterráneos (además de competición entre individuos de una misma especie e individuos aislados sin competidores) fueron sembradas en macetas con dos niveles de fertilización. Se midieron atributos funcionales de la parte aérea y de las raíces de los individuos focales. Para expresar el grado de competición, se consideró la reducción de biomasa en los individuos focales en relación con la de los individuos sin competición, y se modelizó la competición utilizando diferencias en los atributos tanto direccionales (jerarquías) como no direccionales (disimilitud), con y sin consideración de la variabilidad intraespecífica (ITV). Nuestros resultados muestran que las jerarquías de atributos que determinan la competencia entre especies dependieron de los niveles de fertilización, mientras que la disimilitud entre atributos no parece un determinante de importancia en estas relaciones. El efecto negativo de la competición sobre las plantas focales fue directamente proporcional a la altura de las plantas competidoras en ambos niveles de fertilización. Además, en condiciones de alta fertilidad, las plantas con un área foliar especifica (SLA) más baja y raíces más grandes sufrieron menos la competición. Considerar la ITV en las estimaciones de las jerarquías de atributos funcionales mejoró sustancialmente la capacidad predictiva de los modelos. Esta mejora se debió en parte a que la ITV redujo las jerarquías competitivas. Síntesis: Nuestros resultados resaltan la importancia de los atributos funcionales como determinantes de las interacciones entre plantas. Las relaciones de competición entre especies dependen de interacciones complejas entre las diferencias intra e interespecificas en atributos y la disponibilidad de recursos. La ITV aparece como un mecanismo que permite reducir las jerarquías competitivas y por tanto la intensidad de la competición entre plantas.